Sense and Motion: The Barrier Preventing Us from Understanding Motion - Peng Fu, Aaron (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Currently, scientific study and advancements are at odds with the natural motion systems that surround us. This paper explores how it is our sensory form and the cognition developed upon this sensory form that creates a barrier preventing us from truly understanding the laws of motion. It begins by isolating and defining two distinct forms of information and information processing mechanisms: motion information and integrated information. From this new perspective, it then explains how our sensory system is necessarily based on an integrated information mechanism to support basic survival needs, but is essentially blind to the true features of motion. The far-reaching effects of this discovery include the limitations within our cognitive mode and the current methods of scientific study and development.